2010
DOI: 10.1021/bi1002629
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Catalytic Specificity in Alanine Racemase from Quantum Mechanical and Molecular Mechanical Simulations of the Arginine 219 Mutant

Abstract: Alanine racemase (AlaR) catalyzes the interconversion between l-Ala and d-Ala with the aid of the cofactor pyridoxal 5'-phosphate (PLP). The pyridine nitrogen in PLP in the wild-type enzyme is unprotonated due to interaction with Arg219, a rare feature among PLP-dependent enzymes. Herein, we performed combined quantum mechanics and molecular mechanics molecular dynamics simulations to study the Arg219Glu mutant AlaR. In this form of the enzyme, the PLP-pyridine nitrogen is protonated. This study suggests that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 62 publications
0
24
0
Order By: Relevance
“…In search of Alr inhibitors, Mobashery and Johnston 60À62 prepared and investigated the reactions of the peptidyl (24)(25)(26) and amino acid (27,28) (Figure 17) C 10 -esters of deacetylcephalothin with purified enzymes in vitro. Compound 27 showed timedependent inactivation of E. coli Alr in a process that requires O-lactamase for the initial liberation of b-chloro-L-alanine from the cephalosporin.…”
Section: Inhibitors Of Alanine Racemasementioning
confidence: 99%
See 1 more Smart Citation
“…In search of Alr inhibitors, Mobashery and Johnston 60À62 prepared and investigated the reactions of the peptidyl (24)(25)(26) and amino acid (27,28) (Figure 17) C 10 -esters of deacetylcephalothin with purified enzymes in vitro. Compound 27 showed timedependent inactivation of E. coli Alr in a process that requires O-lactamase for the initial liberation of b-chloro-L-alanine from the cephalosporin.…”
Section: Inhibitors Of Alanine Racemasementioning
confidence: 99%
“…Reprotonation on the opposite side of the a-carbon carbanion produces the opposite enantiomer of the alanine substrate whereas reprotonation on the original side of the carbanion by the protonated Lys39 "-amino group yields the same enantiomer of alanine as that of the substrate. There are several reports describing either the role of Lys39, Arg219, and Tyr265 0 residues 24,[26][27][28] in the enzyme catalytic steps or substrate analogs used in structural studies to date 20,[29][30][31][32][33][34] . The structures of Alr with the covalent inhibitors alanine phosphonate and D-cycloserine showed that the inhibition of Alr was due to the formation of a stable covalent linkage with PLP 22,35 .…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to understand the role of protonation of the pyridine nitrogen in PLP, we also studied the Arg219Glu mutant [66]. In this mutant, the pyridine nitrogen interacts with the Glu residue, necessitating a protonated state.…”
Section: Resultsmentioning
confidence: 99%
“…56 Therefore, the main catalytic effect of PLP in AlaR may be ascribed to solvation. [59][60][61] It has been assumed that in such an enzyme the non-protonated form generates an intermediate with a limited lifetime which aids the enzyme in avoiding side reactions. 62 Quantum mechanical and molecular dynamics simulations were recently carried out on the wild type and Arg219Glu mutant.…”
mentioning
confidence: 99%